Effect of different INMS treatments on growth, yield, quality, nutrient uptake and economics of hybrid cotton (Gossypium hirsutum L.) - Gudadhe, N. N.; Dake, A. P.; Lambade, B. M.; Jibhkate, S. B. (Annals of Agricultural Research, 2016)
The field experiment was conducted during summer seasons of 2006-07 and 2007-08 at the research farm, Department of Agronomy, MPKV, Rahuri, Dist. Ahmednagar (MS) to find out the effect of different integrated nutrient management treatments on growth, yield, quality, economics and nutrient uptake of hybrid cotton cv. Phule-492. The experiment with seven treatments viz. T1 : Gross recommended dose of fertilizer i.e.10 t farm yard manure (FYM) ha- 1 + recommended dose of fertilizer (RDF) as 100:50:50 kg NPK ha-1, T2 : 75% RDF+25 % recommended dose of nitrogen (RDN) through vermicompost, T3 : 50% RDF + 50% RDN through vermicompost, T4 : 25% RDF +75% RDN through vermicompost, T5 : 100 % RDN through vermicompost, T6 : fertilizer dose according to soil test crop response ( STCR) equation and T7 : Control, was laid-out in a randomized block design with three replications. The application of fertilizers according to soil test crop response (STCR) equation recorded significantly higher plant height, monopodial branches, sympodial branches and dry matter plant-1 , seed cotton yield, stalk yield, monetary returns and nutrient uptake during both the years of experimentation. Application of different INM treatments did not show significant influence on quality parameters i.e ginning percentage, uniformity ratio, bundle strength, 2.5 per cent span length, maturity coefficient and fibre fineness. Significantly lowest values for growth attributes, seed cotton yield, stalk yield, monetary returns and nutrient uptake was recorded by the control